Factors Affecting the Career Plateau Mediated Job Satisfaction - Lina Kristan Purnawanti; Alimuddin Rizal (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze and explain the influence of personality and work motivation on job satisfaction, to analyze and explain the influence of personality and work motivation on the career plateau mediated by job satisfaction. This study uses an explanatory research type, which tries to explain the relationship between the variables contained in the study. The variables in the research are personality, motivation, job satisfaction and career plateau. The analysis technique in this research is to use instrument test, multiple linear regression, model test, hypothesis testing with SPSS version 22.0 program.The results of this study affect and have a positive effect on employee job satisfaction. Personality has a positive effect on career paths, motivation has a negative effect on career paths, job satisfaction has no significant effect on career paths, because job satisfaction has no effect on career paths, mediation tests cannot be carried out.